Double Taxation Conventions in Romania Case: Dsss Râșnov vs. Anaf Brașov - DUMITER, Florin; JIMON, Ștefania; BOIÈšĂ, Marius (Journal of Legal Studies, 2017)
Conventions to avoid double taxation are the panacea of tax law, lato sensu, and direct taxation, stricto sensu. Although the current network of double taxation conventions has over 2500 tax treaties concluded by the world's states, there are still issues that need to be addressed in their application: the anti-abuse provisions to be found in conventions, the practices of the type treaty shopping, LOB clauses, use of arbitration in the application of double taxation avoidance conventions. The case of Romania is analyzed in this article, through the DSSs Râșnov cause vs. ANAF Brasov, in order to highlight the way in which the framework of the double taxation avoidance convention is applied in Romania, if there are differences and divergences between the de jure provisions of the double taxation avoidance conventions and the de facto application, in practice, a state like Romania, which is in the process of catching up with economies in developed countries. The case presented in this article suggests that there is still room for maneuver to improve the framework for double taxation avoidance conventions in Romania and how they are applied in practice, which their provisions are interpreted and respected.